مهارات التفكير الناقد المتضمنة في كتاب قواعد اللغة العربية للصف السادس الإعدادي ومدى اكتساب الطلبة لها (Journal of the College of Basic Education, 2022)
This study aimed to determine the critical thinking skills that must be available in the Arabic grammar book for the sixth preparatory grade, to know the availability of these skills in the content of the Arabic grammar book, and the extent to which students acquire them. The study included the following question:1- What are the critical thinking skills What must be available in the Arabic grammar book, and the extent to which students acquire it? The text of the book of Arabic grammar approved by the Ministry of Education for the year 2020-2021 AD. It is a book taught to middle school students in Iraq. The study sample consisted of (100) middle school students in Kirkuk governorate. The researcher used the descriptive analytical approach, with the aim of collecting and interpreting information about the Arabic grammar book, and in this broadcast he used several tools, namely: preparing a list of the skills of critical thinking in order to use the list in analyzing Gouda's Arabic language book, and he also used the content analysis tool, which was used to download The Arabic grammar book for the sixth preparatory grade, in the light of critical thinking skills, the researcher also used a test to measure the extent to which the medical skills acquired critical thinking skills found in the book, which include: the preparatory grade. The chapter was chosen randomly, and it was found from the analysis that the list and critical thinking skills were included. Curricula The researcher used frequencies, percentages and correlation coefficient as statistical methods for processing broadcast data: For the critical thinking test tool: the researcher used percentages, the positive mean, and the regressive mean. It is related to content analysis in the light of critical thinking skills: the discussion evaluation skill got a percentage (45%), while the interpretation skill got (37%), and the deduction skill got a percentage (18%), and the critical thinking test: The results indicated a tool for the sample members to test critical thinking skills in the sixth preparatory grade, which is at the intermediate level, where the performance rate was (60%). The level of competition evaluation skill was the highest (65%). While the skill level of change was in the second place by (57%), and in the guest level, it was deduction by (32%). It was also found that there are statistically significant differences in the level of critical thinking skills in the Arabic grammar book for sixth grade students.